1983
DOI: 10.1289/ehp.8353115
|View full text |Cite
|
Sign up to set email alerts
|

Relative source contributions of diet and air to ingested asbestos exposure.

Abstract: Reliable assessments of the relative contributions of diet (food, beverages, and orally administered drugs) and air (inhaled fibers) to total ingested asbestos exposure are not feasible due to the paucity of quantitative data on the subject. Instead, scenarios for both modes of exposure were developed from the limited information available to give crude estimates of ingestion of asbestos from these routes. They suggest that such sources are potentially significant relative to the contribution of asbestos expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Thus, he might have ingested a large amount of asbestos fibers. Asbestos ingestion via food intake [ 44 ] or transport of the chemical to the stomach via respiration [ 45 ] has been suggested to cause gastric cancer. It has also been reported that gastric cancer development associated with chrysotile is more frequent than that with crocidolite [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, he might have ingested a large amount of asbestos fibers. Asbestos ingestion via food intake [ 44 ] or transport of the chemical to the stomach via respiration [ 45 ] has been suggested to cause gastric cancer. It has also been reported that gastric cancer development associated with chrysotile is more frequent than that with crocidolite [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asbestos fiber from cement pipelines results in an average of 1 μm fiber pieces due to natural erosion [38]. Furthermore, diet supplies (food, beverages, and orally administered drugs) contaminated by asbestos in water or airborne must also be considered as a possible source to GI cancer [39]. …”
Section: Epidemiological Evidence: Gastrointestinal Cancers With Asbementioning
confidence: 99%
“…“Unknown” exposures indicate the data came from occupational exposure matrices, including textiles, insulation, or cement workers. Sources: a Haque, 1992; 1996; 1998; Tsurikova, 1992. b Haque, 2001. c Schneider, 1977. d Saat, 1980; Dopp, 1997; Stevens, 1983. e Germani, 1999; Langseth, 2004; Magnani, 2008; Pira, 2005; Reid, 2009; Acheson, 1982; Newhouse, 1985; Wignall, 1982; Berry, 2000. f Millette, 1983. g Graham, 1967. h Attanoos, 2000. i Polissar, 1982.…”
Section: Reproductive and Developemental Effects Of Asbestosmentioning
confidence: 99%
“…However, a cell-mediated immunity towards primary rat fetal cells from rats with Canadian chrysotile B fiber-induced mesothelioma was observed ( Stevens et al, 1983 ), suggesting a link between fetal death and the immune system. In addition, a decrease in surface labeling of glycolipids and glycoproteins in hamster embryos treated with chrysotile asbestos was noted ( Saat et al, 1980 ), along with a rise in micronucleated human amniotic cells ( Dopp et al, 1997 ). Furthermore, incubation of rat embryo cells with crocidolite for 2–48 h resulted in an increase in DNA strand breakage within 2–6 h ( Libbus et al, 1989 ).…”
Section: Reproductive and Developemental Effects Of Asbestosmentioning
confidence: 99%